TRANSFORMASI FUNGSI TEPIAN SUNGAI “TUKAD BADUNG” TINJAUAN POLA PENGGUNAAN RUANG PADA TAMAN KUMBASARI: Transformation of The “Tukad Badung” Riverside Function A Review of Space Utilization Patterns in Kumbasari Park - Praganingrum, Tjokorda Istri (Ganec Swara, 2025)
This study analyses the transformation of functions and patterns of space use along the banks of Tukad Badung, Denpasar, following revitalisation. Historically, urban rivers have often been degraded into dirty and dysfunctional ‘backyards’ as a result of rapid urbanisation. In Denpasar, Tukad Badung experienced similar conditions, with dirty banks and minimal facilities. To address this issue, the Denpasar City Government initiated a revitalisation project that transformed the slum area into an aesthetic and functional public space. This revitalisation successfully changed the image of Tukad Badung from an avoided area to a popular destination. Before revitalisation, this area was only used sporadically for informal activities such as dumping rubbish and fishing. However, after the transformation, the patterns of space use shifted significantly. The area is now a centre for recreation, social interaction, and arts and cultural activities. This improvement was driven by several key factors, namely: increased physical and aesthetic appeal, the availability of adequate public facilities, the emergence of organised economic and commercial activities, strategic accessibility, and an improved perception of safety and cleanliness. Overall, this study concludes that planned physical interventions can fundamentally change the function of an area and the spatial behaviour of the community. The transformation of Tukad Badung demonstrates the success in converting ‘spare space’ into a dynamic ‘third space’, showing that successful urban development lies not only in physical achievements, but also in the ability to create socially inclusive and sustainable spaces.